Fine Manual Dexterity Assessment After Autologous Neural Cell Ecosystem (ANCE) Transplantation in a Non-human Primate Model of Parkinson's Disease. (July 2019) - Borgognon, Simon; Cottet, Jérôme; Moret, Véronique; Chatagny, Pauline; Carrara, Laura; Fregosi, Michela; Bloch, Jocelyne; Brunet, Jean-François; Rouiller, Eric M.; Badoud, Simon
Background . Autologous neural cell ecosystem (ANCE) transplantation improves motor recovery in MPTP monkeys. These motor symptoms were assessed using semi-quantitative clinical rating scales, widely used in many studies. However, limitations in terms of sensitivity, combined with relatively subjective assessment of their different items, make inter-study comparisons difficult to achieve. Objective . The aim of this study was to quantify the impact of MPTP intoxication in macaque monkeys on manual dexterity and assess whether ANCE can contribute to functional recovery. Methods . Four animals were trained to perform 2 manual dexterity tasks. After reaching a motor performance plateau, the animals were subjected to an MPTP lesion. After the occurrence of a spontaneous functional recovery plateau, all 4 animals were subjected to ANCE transplantation. Results . Two of 4 animals underwent a full spontaneous recovery before the ANCE transplantation, whereas the 2 other animals (symptomatic) presented moderate to severe Parkinson's disease (PD)-like symptoms affecting manual dexterity. The time to grasp small objects using the precision grip increased in these 2 animals. After ANCE transplantation, the 2 symptomatic animals underwent a significant functional recovery, reflected by a decrease in time to execute the different tasks, as compared with the post-lesion phase. Conclusions . Manual dexterity is affected in symptomatic MPTP monkeys. The 2 manual dexterity tasks reported here as pilot are pertinent to quantify PD symptoms and reliably assess a treatment in MPTP monkeys, such as the present ANCE transplantation, to be confirmed in a larger cohort of animals before future clinical applications.